MITOS DAN RITUAL DIBALIK TRADISI ZIARAH WALI: STUDI KASUS DI MAKAM SYAIKHONA KHOLIL BANGKALAN - Miftahur Roifah (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2023)
The Indonesian Muslim community continues to uphold its religious traditions to this day. One of the religious traditions carried out is the pilgrimage of saints. Religious traditions are practiced as a basic moral against the influence of modernization. The existence of the Wali pilgrimage is inseparable from the growing faith among the Indonesian Muslim community. The purpose of this study is to explore the phenomenon of religious tradition, namely the pilgrimage of saints. In particular, it examines the myths that have evolved in the Muslim community to continue the Wali pilgrimage tradition to this day. In addition, the study also aims to examine whether the rituals performed by pilgrims are based on cultural or religious values. The location of the Guardian Tomb that is the subject of this investigation is the tomb of Syaikhona Kholil in Bangkalan, Madura. This study is a field survey using descriptive and qualitative ethnographic research techniques. The results of this research show that a myth has developed in which pilgrims believe that if they pray at a saint's tomb, their prayers will be easily answered. Apart from that, pilgrims believe that if they pray at the tomb of a saint, they will easily overcome all difficulties in life. It's a ritual. These rituals include: ablution, praying, reading greetings, praying, reading Yasin and tahlil, reading dhikr and sholawat, reading prayers and listening to lectures.